ALAT PENGISIAN DAN PEMANTAUAN KETERSEDIAAN BAHAN BAKAR MINYAK DENGAN MENGGUNAKAN SENSOR PING DAN FLOW SENSOR - Gulo, Yamanotona; Irawan, Irawan; Irawan, Hendri (Universitas Budi Luhur, 2025)
In Indonesia, fuel filling stations (SPBU) play an important role in the energy supply chain that supports community and economic mobility. Gas station management needs to focus on service quality and fuel availability for consumers. However, misuse by irresponsible parties often occurs, such as manipulation of the amount of fuel sold. This causes consumers to receive an amount of fuel that does not correspond to their payment, harming them and reducing the reputation of gas station managers. Technical errors, such as damage to dispensing machines, can also disrupt distribution. To overcome this problem, this research aims to develop a fuel monitoring and filling tool that uses a PING sensor and flow sensor. This sistem utilizes Internet of Things (IoT) technology to connect sensors in the tank and pump. Data from the sensors is sent to the Blynk platform for analysis. This real-time monitoring is expected to increase efficiency, accuracy and reliability of fuel distribution and reduce the potential for fraud. By implementing this sistem, consumers can feel more secure and confident that the fuel they receive is what they paid for.